Beyond the Workplace: How Psychological Empowerment Influences Employee Creativity in the Saudi Hotel Sector—The Mediating Role of Affective Commitment and the Moderating Role of Psychological Safety - Ahmed Mohamed Hasanein; Musaddag Elrayah (European Journal of Investigation in Health, Psychology and Education)
Businesses in the hotel and hospitality sectors face significant challenges when they lack originality and creativity. Creativity and innovative behavior are both necessary to increase employee effectiveness. This study aims to investigate how psychological empowerment (PEMP) directly affects employee creativity (EC) and affective commitment (AC) in the Saudi hotel industry. Additionally, this study examines the moderating function of psychological safety (PS) and the mediating role of affective commitment. Data were collected through an online cross-sectional survey of a purposive sample of 536 operational staff at hotels in the Eastern Region of Saudi Arabia. Structural equation modeling was used to test the proposed framework (PLS-SEM). Surprisingly, these findings revealed no significant direct effect of PEMP on EC. However, AC has emerged as a crucial mediating mechanism through which PEMP indirectly fosters creativity. Furthermore, psychological safety (PS) is found to moderate the PEMP–EC relationship, enhancing its impact under favorable conditions. These results highlight the theoretical and practical significance of emotional commitment as a conduit for empowering employees to engage in creative behavior. This study offers new insights into how psychological and organizational factors interact to shape creativity in the hospitality context.